MP25: The role of advanced imaging in the management of benign headaches in the emergency department: a systematic review. (15th May 2017) - Lepage, R.; Krebs, L.; Kirkland, S.W.; Alexiu, C.; Campbell, S.; Rowe, B.H.
Abstract : Introduction: Headache is a common emergency department (ED) presentation. Benign (i.e., non-pathological) headaches are particularly common, including exacerbations of chronic migraine, tension, and cluster headache. Several studies have reported concerns over the frequent use of advanced imaging, specifically computed tomography (CT), in the ED management of benign or primary headache presentations. This systematic review examined the proportion of adult ED benign headache presentations who receive a CT(head).Methods: Eight bibliographic databases and the grey literature were searched. All studies reporting the proportion of benign headache patients receiving a CT(head) in the ED were eligible for inclusion. Studies which included a secondary headache population of 15% of their total study population or less where eligible for inclusion. Two reviewers independently assessed study inclusion and completed quality assessment and data extraction. Weighted medians were calculated for the primary and secondary outcomes, as appropriate.Results: The search returned 2, 444 unique citations, of which 20 met the inclusion criteria (21 patient groups were analyzed). The majority of the studies were descriptive in nature and conducted in North America. The reported proportion of benign headache patients receiving a CT(head) varied considerably (range: 2.06-67.21%); with a weighted median of 30.0% (interquartile range: 30.0, 30.0). Studies published in 2000 or later (18/21 groups) were found to have a higher weighted median percentage compared to those published pre-2000 (p=0.016). Neither the country of origin nor the proportion of patients with secondary headache included within the study population had a significant effect on CT utilization. Of the three studies which reported the discharge diagnosis of all patients, sub-arachnoid hemorrhage was discovered in 2/241 (0.83%) of CT scans.Conclusion: Considerable variation in CT utilization for benign headache ED presentations exists and estimates indicate that more than a quarter of patients receive a CT(head). Overall, these CT scans rarely identify significant pathology, suggesting imaging may be safely reduced. Further research is required to identify interventions which can safely and effectively reduce unnecessary imaging among headache presentations.